Implementasi Metode QCC untuk Menurunkan Jumlah Sisa Sampel Pengujian Compound - Khamaludin Khamaludin Khamaludin; Anang Pandan Respati (Jurnal Optimasi Sistem Industri, 2019)
In the manufacturing industry, the role of quality control or laboratory parts is very important to ensure the quality of raw materials or finished products by testing. Smooth testing carried out by the QC/Lab section will have an impact on the smooth production process. PT. Bando Indonesia is one of the automotive manufacturing industries that is consistent with quality. However, based on April-June 2018 data based on SQCDMP data, it was found that productivity factors were quite low as indicated by the presence of remaining hardness and specific gravity compound test results reaching 36.44% at the end of each shift. By carrying out corrective actions through the 8 step Quality Control Circle (QCC) and using seven tools as an analytical tool, the results obtained are significant, namely the reduction in the remaining samples of compound testing by only 21.97% and impact on cost, morality, and productivity.